Effects of an immunosuppressive treatment on the rat prostate - Grabowska M; Kędzierska K; Michałek K; Słuczanowska-Głąbowska S; Grabowski M; Piasecka M; Kram A; Rotter I; Rył A; Laszczyńska M (Dove Medical Press, 2016)
Marta Grabowska,1 Karolina Kędzierska,2 Katarzyna Michałek,3 Sylwia Słuczanowska-Głąbowska,4 Maciej Grabowski,5 Małgorzata Piasecka,1 Andrzej Kram,6 Iwona Rotter,7 Aleksandra Rył,1 Maria Laszczyńska1 1Department of Histology and Developmental Biology, Pomeranian Medical University, 2Department of Nephrology, Transplantology and Internal Medicine, Pomeranian Medical University, 3Department of Physiology, Cytobiology and Proteomics, West Pomeranian University of Technology, 4Department of Physiology, Pomeranian Medical University, 5Department of Microbiology and Applied Biotechnology, West Pomeranian University of Technology, 6Department of Pathology, West Pomeranian Oncology Center, 7Department of Medical Rehabilitation, Pomeranian Medical University, Szczecin, Poland Abstract: The aim of this study was to determine the influence of different combinations of immunosuppressive drugs on the morphology, ultrastructure, and expression of proliferating cell nuclear antigen and cytoskeleton proteins in the rat dorsolateral prostate. The studies were conducted on 48 male Wistar rats. The animals were divided into eight groups: a control group and seven experimental groups. For 6 months, the animals in the experimental groups were administered a combination of drugs including rapamycin (Rapa), cyclosporin A, tacrolimus (Tac), mycophenolate mofetil, and prednisone (Pred), according to the standard three-drug regimens for immunosuppressive therapy used in clinical practice. An evaluation of the morphology and ultrastructure was conducted, and a quantitative evaluation of the expression of proliferating cell nuclear antigen and desmin- and cytokeratin-positive cells with weak, moderate, and strong expression was performed. The combination of Rapa, Tac, and Pred caused the smallest morphological and ultrastructural changes in the rat prostate cells. In the case of rats whose treatment was switched to Rapa monotherapy, a decreased percentage of proliferating cells of both the glandular epithelium and the stroma was found. Decreases in body weight and changes in the expression of cytokeratin and desmin were observed in all the experimental rats. The combination of Rapa, Tac, and Pred would seem to be the most beneficial for patients who do not suffer from prostate diseases. Our results justify the use of inhibitors of the mammalian target of Rapa in the treatment of patients with prostate cancer. The changes in the expression of cytoskeleton proteins may be the result of direct adverse effects of the immunosuppressive drugs, which are studied in this article, on the structure and organization of intermediate filament proteins. Keywords: rat prostate, ultrastructure, cytokeratin, desmin, PCNA, immunosuppressants